PSYCHOSOMATICS OF GASTRITIS (Modern American Journal of Medical and Health Sciences, 2025)
The article examines the influence of psychoemotional factors on the development and course of gastritis. The relationship between stress, anxiety, suppressed emotions and disorders in the gastrointestinal tract is analyzed. The mechanisms of psychosomatic effects are considered, including the effect of stress on gastric juice production, gastric motility and microflora.